PRINCIPLES OF SELECTION OF AUTHENTIC MATERIALS IN TEACHING UZBEK AS A FOREIGN LANGUAGE - Asilova, Gulshan (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
From year to year, interest in learning the Uzbek language has grown around the world. Unlike languages widely spoken in the world, the methodology of teaching Uzbek as a foreign language does not yet have rich experience. The process of teaching Uzbek to speakers of other languages and the problems arising in the process are not yet well studied by researchers. Educational literature on the Uzbek language created so far for foreigners cannot be considered sufficient as well. Particularly, there are several study guides and electronic complexes that have been created as a result of the experience of teaching Uzbek to English, German, Chinese, Korean, Russian learners. However, to what extent the teaching materials given in them are close to the living language and their effectiveness in developing speaking skills in the Uzbek language has not been studied properly. One of the actual problems in the methodology of teaching foreign languages is the problem associated with the use of authentic materials in the process of education. In this regard, experience has been accumulated from the methodologies of languages that are widely spoken across the world. Experts in this field are mainly concerned with the choice of authentic materials and their effective application in the educational process. This article is devoted to the problems of selecting authentic materials in the Uzbek language, their adaptation in accordance with the language needs of students and their intended use in the teaching process. The article analyzes the features of authentic materials that require attention when working with them, as well as their types that contribute to the effective development of speech in the Uzbek language. Methodological recommendations on the selection of authentic materials for foreign students studying Uzbek are given accordingly.